A STUDY ON HOW LONG AND SHORT SENTENCES SHOW THE STORY’S PACING IN ANTHONY HOROWITZ’S RAVEN’S GATE - System, Administrator; Sidha Karya, I Wayan (Sphota : Jurnal Linguistik dan Sastra, 2019)
Abstract   Long and short sentences affect the reader?s pace of reading story since the have to farce the complexity of the sentences and words used in it. In this study the researcher attempted to see the impact of the use of long and short sentences on the pace of the story as implemented by Anthony Horowitz, a novelist, in his novel Raven?s Gate. Especially the researcher is looking at what types of long and short sentences the novelist is using and how these long and short sentences are building up his story line and their effect on the pace of the story. A sentence with the length of up-to fourteen (14) words is considered to be short and the one over 14 words is considered to be long in spite its grammatical form, whether it is simple or complex. The criteria are based on empirical study as mentioned by Casi Newell in the AJE (American Journal Experts) retrieved from https://www.aje.com/en/arc/editing-tip-sentence-length/, that ?the average sentence length in scientific manuscripts is 12-17 words,? with JK Rowling?the writer of Harry Potter?who can be considered to be representative of a modern English writer with a general audience, having the average of 12 words. For convenience we take the liberty of taking 14 words for the longest sort sentences and those which have 15 or more words are considered to be long sentences. We expect that length of sentences would have significance in revealing the pace of the story through its choice of words and sentence constructions. Key words: pacing, short sentence, long sentence, simple sentence, complex/compound sentence